2013
DOI: 10.1002/jcc.23204
|View full text |Cite
|
Sign up to set email alerts
|

Electronic structure of the S1 state in methylcobalamin: Insight from CASSCF/MC‐XQDPT2, EOM‐CCSD, and TD‐DFT calculations

Abstract: The methylcobalamin cofactor (MeCbl), which is one of the biologically active forms of vitamin B12, has been the subject of many spectroscopic and theoretical investigations. Traditionally, the lowest-energy part of the photoabsorption spectrum of MeCbl (the so-called α/β band) has been interpreted as an S0→S1 electronic transition dominated by π→π* excitations associated with the C=C stretching of the corrin ring. However, a more quantitative band-shape analysis of the α/β spectral region, along with circular… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
57
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 59 publications
(60 citation statements)
references
References 121 publications
3
57
0
Order By: Relevance
“…Their argument is based on the ∼0.3-0.4 eV lowering when going from EOMCCSD to CC3. However, as can be seen in our tables and as shown in previous studies [64,[81][82][83], it is not unusual to observe errors of this magnitude in EOMCCSD calculations for singly excited states. Indeed, the REL values characterising the 2 1 A 1 (π → π * ) and 3 1 A 1 (π → π * ) states of cyclopentadiene, of about 1.153 and 1.055, respectively, when the MP2/6-31G * geometry is employed, show that these states are predominantly oneelectron transitions and that double excitations do not significantly contribute to their wave functions.…”
Section: Unsaturated Cyclic Hydrocarbons: Cyclopropenesupporting
confidence: 51%
See 1 more Smart Citation
“…Their argument is based on the ∼0.3-0.4 eV lowering when going from EOMCCSD to CC3. However, as can be seen in our tables and as shown in previous studies [64,[81][82][83], it is not unusual to observe errors of this magnitude in EOMCCSD calculations for singly excited states. Indeed, the REL values characterising the 2 1 A 1 (π → π * ) and 3 1 A 1 (π → π * ) states of cyclopentadiene, of about 1.153 and 1.055, respectively, when the MP2/6-31G * geometry is employed, show that these states are predominantly oneelectron transitions and that double excitations do not significantly contribute to their wave functions.…”
Section: Unsaturated Cyclic Hydrocarbons: Cyclopropenesupporting
confidence: 51%
“…However, EOMCCSD is not robust enough to obtain a quantitative description of many of such states, especially when larger polyatomic species are examined (cf., e.g., [64,[81][82][83]; for a thorough evaluation of a number of EOMCC methods, including EOMCCSD, illustrating the same, see [17,19,20,22,24,25]). It also fails to describe states with significant double excitation contributions.…”
Section: Introductionmentioning
confidence: 99%
“…The photoexcitation of non-alkyl cobalamins is characterized by formation of short-lived electronically excited states that recover to the ground state on a picosecond timescale with little to no photolysis quantum yield. Time dependent density functional theory (TD-DFT) studies by Kozlowski and coworkers have identified a triplet sigma antibonding state that was suggested to mediate the photolysis of alkyl cobalamins [28,[30][31][32][33][34]. Detailed comparison of MeCbl and ethylcobalamin (EtCbl) led to the suggestion that changes in the barrier for crossing from the S 1 state to the dissociative channel accounted for the distinctive wavelength dependence and photolysis quantum yield following excitation of MeCbl.…”
Section: Introductionmentioning
confidence: 96%
“…Whereas the ground-state structural properties were essentially insensitive with respect to the functional used, in contrast, the excited states were very sensitive to the choice of XC functional. Recent theoretical studies 140,161,163,271 on cobalamins support the use of gradient-corrected functionals, such as BP86, when studying excited states of these systems compared to, for instance, the use of hybrid functionals.…”
Section: Abs CD and Mcd Spectra In Response Theory Td-dft Calculationsmentioning
confidence: 99%
“…109 However, the validity of hybrid functionals with respect to electronic excitations of cobalamins have been questioned 140,161,163,271 and numerical evidence suggests that GGA-type functionals perform better. From these investigations, the S 1 for MeCbl was assigned as a MLCT excitation, whereas LMCT described the lowest excitation of CNCbl, indicating the importance of Co d orbitals in the electronic transitions.…”
Section: Assignment Of Electronic Transitionsmentioning
confidence: 99%